How Useful Are Monogenic Rodent Models for the Study of Human Non-Alcoholic Fatty Liver Disease? - Mann, Jake P.; Semple, Robert K.; Armstrong, Matthew J. (Frontiers in Endocrinology, 2016)
Improving understanding of the genetic basis of human non-alcoholic fatty liver disease (NAFLD) has the potential to facilitate risk stratification of affected patients, permit personalised treatment, and inform development of new therapeutic strategies. Animal models have been widely used to interrogate the pathophysiology of, and genetic predisposition, to NAFLD. Nevertheless considerable interspecies differences in intermediary metabolism potentially limits the extent to which results can be extrapolated to humans. For example, human genome-wide association studies have identified polymorphisms in PNPLA3 and TM6SF2 as the two most prevalent determinants of susceptibility to NAFLD and its inflammatory component (NASH), but animal models of these mutations have had only variable success in recapitulating this link. In this review we critically appraise selected murine monogenic models of NAFLD, NASH, and hepatocellular carcinoma (HCC) with a focus on how closely they mirror human disease.